1995
DOI: 10.1007/bf00004289
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of interrenal function in freshwater and sea water adapted tilapia (Oreochromis mossambicus)

Abstract: In teleosts, cortisol is one of the key factors regulating the adaptation to environmental challenges, such as salinity changes. This paper compares interrenal function between fully adapted freshwater (FW) and sea water (SW) specimens of the euryhaline teleost Oreochromis mossambicus (tilapia), combining morphometric and biosynthetic approaches. Interrenal tissue and two tissues producing interrenal secretagogues (ACTH and A N P; atrial natriuretic peptide) were studied. The results demonstrate that sea water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…These cases generally involve smolt and post-smolt stages which can readily adapt to SW and may involve an increase in the clearance rate of cortisol in SW-adapted fish (Redding et al 1984b;Nichols and Weisbart 1985;Patifio et al 1987;Balm et al 1995). In contrast, the plasma cortisol values obtained for cutthroat trout in this study were more comparable with other salmonid parr stages and non-salmonid species during exposure to saline environments.…”
Section: Discussioncontrasting
confidence: 53%
“…These cases generally involve smolt and post-smolt stages which can readily adapt to SW and may involve an increase in the clearance rate of cortisol in SW-adapted fish (Redding et al 1984b;Nichols and Weisbart 1985;Patifio et al 1987;Balm et al 1995). In contrast, the plasma cortisol values obtained for cutthroat trout in this study were more comparable with other salmonid parr stages and non-salmonid species during exposure to saline environments.…”
Section: Discussioncontrasting
confidence: 53%
“…Although we have observed increases in plasma cortisol during seawater adaptation in agreement with the welldocumented role as a seawater adapting hormone in tilapia and other fish (McCormick, 2001), other reports on blood cortisol in seawater-challenged tilapia have been inconsistent (Morgan et al, 1997;Dean et al, 2003;Kajimura et al, 2004). Despite the unaltered plasma level, Balm et al (1995) reported that the total volume of O. mossambicus interrenal cells increased 10-fold in seawater-adapted fish and was paralleled by an increase in in vitro interrenal cortisol production, indicating a simultaneous elevation in the production/secretion and clearance of cortisol in seawater-acclimated tilapia. Therefore, our long-term cortisol implantation study seems to mimic the cortisol secretion levels seen during seawater challenge.…”
Section: Discussionmentioning
confidence: 93%
“…The common carp is a rather stenohaline fish (Gupta & Hanke 1982), and changes in water salinity increase plasma cortisol levels (Abo & Hanke 1984) which points to a stress response. In euryhaline teleosts also such as the Mozambique tilapia (Oreochromis mossambicus) (Balm et al 1994) and the sea bream (Sparus aurata) (Mancera et al 1994), rapid salinity changes can act as stressors. Moreover, stressors may also affect the integrity of the branchial epithelium, thereby increasing stress (Ultsch et al 1981).…”
Section: Introductionmentioning
confidence: 99%